2003
DOI: 10.1111/j.1469-8137.2004.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular, compound‐specific, and bulk carbon isotope patterns in C3 and C4 plants: a review and synthesis

Abstract: Review SummaryStudies using carbon isotope differences between C 3 and C 4 photosynthesis to calculate terrestrial productivity or soil carbon turnover assume that intramolecular isotopic patterns and isotopic shifts between specific plant components are similar in C 3 and C 4 plants. To test these assumptions, we calculated isotopic differences in studies measuring components from C 3 or C 4 photosynthesis. Relative to source sugars in fermentation, C 3 -derived ethanol had less 13 C and C 3 -derived CO 2 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
327
3
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(357 citation statements)
references
References 86 publications
22
327
3
2
Order By: Relevance
“…Therefore this model assumes that any isotopic fractionation between the litter source and CO 2 , WEOC, and PLFA formation, likely on the order of 1e6 ‰ (Fernandez and Cadisch, 2003;Hobbie and Werner, 2004), as well as any potential fractionation from the temperature treatments, have a negligible contribution to the mixing model. Due to the >23,000‰ difference between the litter and soil end members, this assumption is valid.…”
Section: Isotopic Corrections and Mixing Modelsmentioning
confidence: 99%
“…Therefore this model assumes that any isotopic fractionation between the litter source and CO 2 , WEOC, and PLFA formation, likely on the order of 1e6 ‰ (Fernandez and Cadisch, 2003;Hobbie and Werner, 2004), as well as any potential fractionation from the temperature treatments, have a negligible contribution to the mixing model. Due to the >23,000‰ difference between the litter and soil end members, this assumption is valid.…”
Section: Isotopic Corrections and Mixing Modelsmentioning
confidence: 99%
“…Studies of enzyme-moderated stable isotope fractionation in biological systems have shown that the composition of specific compounds can be strongly influenced by the 13 C/ 12 C of their precursor carbon source, and any subsequent biochemical kinetic isotope fractionation caused by carbon fluxes through reaction networks (Hayes, 2001;Hobbie and Werner, 2004;Dungait et al, 2008;Zhou et al, 2015). Tcherkez et al (2011) proposed that the fluxes of carbon through plant metabolic processes can give rise to considerable redistribution of 12 C and 13 C that occurs after carbon is fixed during photosynthesis.…”
Section: Mechanisms That May Influence the Carbon Isotope Compositionmentioning
confidence: 99%
“…C values of lipids relative to bulk tissue in monocots (Hobbie and Werner, 2004). The relationship between lipid concentration and offset among the Stiffkey plants is not straightforward, however.…”
mentioning
confidence: 99%
“…C values for leaf waxes derived from C 3 (about -36.0‰) and C 4 (-21.0‰) plants (16). Carbon isotopic abundances of phenolic monomers of lignin amplify the C 3 -C 4 difference and range between ca.…”
mentioning
confidence: 99%